Hepatitis B vaccination for male sex workers: the experience of a specialist GUM service. Issue 1 (3rd February 2006) - Sethi, G; Holden, B M; Greene, L; Gaffney, J; Ward, H
Abstract : Background: Male sex workers are at risk of blood borne viruses but may have limited access to sexual health services, including vaccination. We explore factors associated with hepatitis B vaccination uptake among male sex workers in London Methods: Follow up study of men attending the Working Men's Project, a specialist health project for men who sell sex, between 1994 and 2003. Results: At baseline 797 men were screened for hepatitis B; 308 were not eligible for vaccination because of past or current infection (155, 19.4%) or previous vaccination 153 (19.2%). Of the 489 men eligible for a full course of vaccination 292 (59.8%) completed the course. Completion rates fell over time: men recruited up to 1999 were more likely to complete the course than those recruited more recently (177/259, 68.3% compared with 115/229, 50.2%, OR 2.14, 95% CI 1.48 to 3.09). Conclusion: This specialist service achieved a high rate of vaccine completion in the early years, but the decline is a concern. It may reflect wider availability of vaccination elsewhere and a more mobile population of sex workers. Shorter courses may achieve a higher completion.